Modern approaches to surgical treatment of thoraco-abdominal wounds - D. G. Amarantov; M. F. Zarivchatskii; A. A. Kholodar; O. S. Gudkov; E. V. Kolyshova (Вестник хирургии имени И.И. Грекова)
Thoraco-abdominal wounds are the most severe injuries of the chest and abdomen, with mortality reaching 13–20 %. The main focus of treatment of such patients is surgical correction of the injuries. Wide range of classical and minimally invasive interventions is used for treatment of victims . The paper presents the range of views of modern researchers on the indications for laparocentesis, drainage of the pleural cavity, thoracoscopy and laparoscopy, thoracotomy and laparotomy in this pathology. The opinions of various researchers on the optimal combination of interventions and tactics of surgical treatment of victims with thoraco-abdominal wounds are presented. It is necessary to continue the search for optimal combinations of classical and minimally invasive interventions in relation to a variety of clinic situations that arise in the treatment of patients with thoraco-abdominal wounds.